Macroeconomic effects of COVID-19 in a commodity-exporting economy: Evidence from Mongolia - Gan-Ochir Doojav (Asian Development Bank Institute (ADBI), 2022)
This paper examines macroeconomic effects and transmission mechanisms of COVID19 in Mongolia, a developing and commodity-exporting economy, by estimating a Bayesian structural vector autoregression on quarterly data. We find strong cross-border spillover effects of COVID-19. Our estimates suggest that the People's Republic of China's GDP and copper price shocks account, respectively, for three-fifths and one-fifth of the drop in real GDP in 2020Q1. The recovery observed for 2020Q2-2021Q1 is primarily due to positive external shocks. However, disruptions in credit and labor markets have been sustained in the economy. Two-thirds of the fall in employment in 2021Q1 could be attributed to adverse labor demand shocks. We also reveal novel empirical evidence for the balance sheet channel of the exchange rate, the financial accelerator effects, and an indirect channel of wage shock to consumer price passing through bank credit.
Keywords: C32; E6; E17; E27; E32; I15; 330; COVID-19; demand and supply shocks; macroeconomic fluctuations; structural vector autoregression; Bayesian analysis